PENGARUH PEMBIAYAAN MODAL KERJA TERHADAP PENDAPATAN USAHA NASABAH PADA PT. BANK SYARIAH MANDIRI KANTOR CABANG SIMPANG PATAL PALEMBANG - Erdah Litriani (I-Finance Journal, 2017)
This study aims to investigate the Working Capital Financing Effect Against Revenue Customer At PT. Bank Syariah Mandiri Branch Office Simpang Patal Palembang. Working capital financing is financing to meet the needs of increased production both quantitatively and qualitatively, and for the purposes of trade or increase the utility of place of an item. Operating revenues were higher course is expected by every customer who makes an effort to encourage the development of the business. This study on the financing of working capital to revenue customers by using purposive sampling method means sampling conducted choose subjects based on specific criteria researchers set, the sample in this study were 30 people from a population of 274 people. The method used in this study is a simple linear regression method. Based on the research results obtained, that the financing of working capital variables affect the customer's business income variable and there is a positive relationship between working capital financing to operating income customers. Based on t test results that show the value of t> t table (8.937> 1.701) and a significant value is smaller than the significance level (α) 0.05 (0.000 <0.05), then the hypothesis that there is a significant positive effect variable financing working capital to operating income customers at PT. Bank Syariah Mandiri Branch Office Simpang Patal Palembang.